Hollywood salutes Canadian animation [videorecording]. - National Film Board of Canada ([Montreal] NFBC, 1979)
Seven NFBC productions have won the Oscar Academy Awards of Motion Picture for Arts and Sciences.
Every child, Oscar 1980 (6 min.) -- The Sand castle, Oscar 1978 (13 min.) -- The House that Jack built, Nominee 1969 (10 min.) -- Special delivery, Oscar 1979 (7 min.) -- Walking, Nominee 1970 (5 in.) -- The Street, Nominee 1977 (10 min.) -- Neighbors, Oscar 1953 (10 min.)
Keywords: Animated films -- Canada; Academy Awards (Motion Pictures).; Theater art